Tempo de passagem de sementes pelo trato digestório de aves frugívoras, uma primeira avaliação no Brasil - Gasperin, Gabriel (2012)
The transit time of seeds ingested by frugivorous animals has important implications for the spatial distribution of seeds and their dispersal distance. Nevertheless, this parameter is rarely included in seed dispersal studies. In this paper, we provide information about the transit time of seeds of nine species of plants ingested by individuals of six species of captive birds (Turdus albicollis, T. amaurochalinus, T. leucomelas, T. rufiventris, Stephanophorus diadematus and Saltator similis). We found that (1) seeds are regurgitated quickly through the digestive tract of birds than defecated seeds, and (2) large seeds (e.g., > 5 mm in diameter for Turdus spp.) are regurgitated rather than defecated. These results corroborate other studies, but the relationship between seed size and transit time seems to be quite complex and variable, requiring more detailed studies on this important aspect of the ecology of seed dispersal and digestive physiology of frugivorous birds.